Teaching chemistry in the metaverse: the effectiveness of using virtual and augmented reality for visualization - Amirbekova, Elmira; Shertayeva, Nailya; Mironova, Ekaterina (Frontiers in Education, 2024)
The metaverse is a promising platform for learning that all participants in the teaching and learning process may find appealing. This study aims to investigate the effectiveness of using metaverse-related visualization technologies, such as Virtual Reality (VR) and Augmented Reality (AR), in teaching chemistry. The study has an experimental research design and uses the following tools to collect data: Dombrovskaya's Motivation for Learning Scale, the SAMOAL Questionnaire, and the Self-management Questionnaire. The study sample includes 236 first-year undergraduate students studying chemistry at the Faculty of Natural Sciences.Results suggest that the integration of immersive VR/AR technologies in chemistry education signifies the beginning of a metaverse transition; the process, however, is in its early stages.The study concludes that immersive VR/AR technologies have an advantage over traditional programs in terms of motivation and competence development. Future research can investigate the impact of VR/AR technologies on students' anxiety and build a model for predicting student achievements in the metaverse-based chemistry classroom.